Implementasi Budaya Kerja Dan Gaya Kepemimpinan Terhadap Peningkatan Kinerja Karyawan - Anggada Abim Pramudya; Muhammad Rouf Purnama; Ninnes Sri Andarbeni; Putri Nurjayanti; M. Isa Anshori (Institut Nalanda, 2023)
In the goal for the development of the organization many factors must be pursued. One of them is work culture. It is important for an organization to pay attention to and follow the culture that is and will continue to run, and develop in order to continue to control the culture that continues to run in a positive and profitable direction for the organization. Culture has a very important potential to have an effect on the organization. Work culture is one of the supporting factors for the organization to develop. Work culture is created from the habits adopted by the organization to be used as a reference for where the organization's goals are running. The application of work culture in the organization has a very important role because it relates to the attitudes and behavior of human resources in the organization. Culture includes general management policies, procedures, strategic objectives and actions. In its application, each company has a different culture, this is what distinguishes one company from another. Culture can be said to be an image for the company, therefore it needs to be directed in a positive direction in order to have a positive impact and image for the organization. The development and management of a good culture requires the role of a leader, without a leader an organization will not be able to run towards its goals. Leadership style is very important for leaders to manage the HR they lead with their respective assigned tasks. This study aims to determine the relationship between work culture and leadership style to improve employee performance in the company using a literature study approach. Which approach to literature study is carried out by collecting and reviewing theoretical references that are in accordance with the case obtained. So that the results of the literature review obtained show that work culture and leadership style have a positive and significant impact on improving employee performance. Leadership will be a determining factor for success in a company. This is because leadership is the focal point of significant change in the company, leadership becomes an impactful personality. Leadership is an art in creating corporate fit and stability.